When Naked Means Naked: An Experiential Journey (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper will explore the reality of how being naked in a therapy session could be accommodated by using an existential approach, and by examining the experiences of established therapists working with nakedness as part of the therapeutic process. I will be referring to the existential philosophers who have provided a framework in considering this potentially unconventional situation. I will also share my own experience of a client being naked in therapy and its subsequent significance in advancing the therapeutic process.
Keywords: Freedom; transcendence; openness; relatedness; ontological security